1999
DOI: 10.1034/j.1399-3003.1999.14d03.x
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillatory ventilation is not superior to conventional mechanical ventilation in surfactant-treated rabbits with lung injury

Abstract: High-frequency oscillatory ventilation is not superior to conventional mechanical ventilation in surfactant-treated rabbits with lung injury. D. Gommer, A. Hartog, R. Schnabel, A. De Jaegere, B. Lachmann. #ERS Journals Ltd 1999. ABSTRACT: The aim of this study was to compare high-frequency oscillatory ventilation (HFOV) with conventional mechanical ventilation (CMV) with and without surfactant in the treatment of surfactant-deficient rabbits. A previously described saline lung lavage model of lung injury in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…HFOV used without the open lung strategy was relatively ineffective in reducing lung injury 73 and several animal studies have indicated that conventional ventilation, when used with the OLC, can achieve similar degrees of lung protection as HFOV, suggesting that optimizing lung volume, rather than frequency, is the key factor. [74][75][76] Clinical application of the OLC with conventional ventilation, however, may not be an easy task and has not been extensively evaluated in clinical trials. 77 Fig.…”
Section: High-frequency Ventilationmentioning
confidence: 98%
“…HFOV used without the open lung strategy was relatively ineffective in reducing lung injury 73 and several animal studies have indicated that conventional ventilation, when used with the OLC, can achieve similar degrees of lung protection as HFOV, suggesting that optimizing lung volume, rather than frequency, is the key factor. [74][75][76] Clinical application of the OLC with conventional ventilation, however, may not be an easy task and has not been extensively evaluated in clinical trials. 77 Fig.…”
Section: High-frequency Ventilationmentioning
confidence: 98%
“…By contrast, the importance of optimizing lung inflation has long been recognized by users of high-frequency ventilation, where the optimal lung volume strategy has become standard practice and is widely understood to be the key to its success. However, although there are a number of animal studies indicating that conventional ventilation with the OLC can achieve similar degrees of lung protection as high-frequency oscillatory ventilation (HFOV), suggesting that optimizing lung volume rather than frequency is the key factor, [32][33][34][35][36] the clinical application of the OLC with conventional ventilation has not been extensively evaluated in clinical trials. 37 Finally, it is important to understand that there is no single 'safe' PEEP level.…”
Section: Clinical Trials Of Synchronized Ventilationmentioning
confidence: 99%
“…Recent animal studies have come to different conclusions as to whether the combination of optimal lung volume strategy achieved by HFOV with surfactant is superior to the lungprotective strategy of CMV with higher PEEP and smaller tidal volumes, in terms of more uniform lung inflation, attenuation of the loss of pulmonary compliance, less pulmonary inflammation, and reduction of the conversion of large surfactant aggregates into smaller aggregate forms. Some of these studies favored HFOV [32][33][34], others showed equal effectiveness of CMV and HFOV as long as the open lung concept was satisfied [35][36][37][38].…”
Section: Animal Experimentsmentioning
confidence: 99%